BURN SHOCK IN PEDIATRIC AFTER THERMAL INJURY AND MULTIPLE ORGAN FAILURE SYNDROMES - Haydarov Musomiddin Muxammadievich; Melikova Dilshodaxon Uktamovna; Siddikov Olim Abdullaevich; Muradova Raila Rustamovna; Begnaeva Mukhiba Usmanovna (Scholar Express Journals, 2022)
Burns covering more than one-third of the total body surface area lead to the unique derangements of cardiovascular function known as burn shock. Burn shock results from the interplay of direct tissue injury, hypovolemia, and release of multiple mediators of inflammation. The course and treatment of 56 pediatric patients with burn shock have been analyzed. With the purpose of investigation all patients with burn shock were subdivided into 2 groups: The first (control) 23 children and was treated according to traditional antishock infusion-transfusion therapy without inotropic therapy. The second (basic) group included 33 patients with burn shock and underwent a complex, antishock infusion-transfusion therapy with employment of inotropic and organoprotective therapy depending on dysfunction of vitals and systems. The victims of burns - material prove high spread POI in patients with burns, that requires complex, purposeful conservative (local and general) and surgical treatment for its reduction and prevention of unfavorable results
Keywords: Burns shock; treatment; antishock infusion-transfusion; covering